Influence of chronic kidney disease and its severity on the efficacy of semaglutide in type 2 diabetes patients: a multicenter real-world study - García de Lucas, María Dolores; Caballero, Irene; Fernández-García, José Carlos; Domínguez-Rodríguez, Manuel; Moreno-Moreno, Paloma; Jiménez-Millán, Anabel; Botana-López, Manuel; Avilés, Beatriz; Merino-Torres, Juan Francisco; Soto, Alfonso; Tejera, Cristina; Morales, Cristóbal (Frontiers in Endocrinology, 2023)
Semaglutide is a glucagon-like peptide 1 receptor agonist that improves glycemic control and achieves weight loss in type 2 diabetes (T2D) patients. Subcutaneous (s.c.) semaglutide at 1 mg once weekly (OW) is safe in T2D patients with chronic kidney disease (CKD). Whether or not CKD and its severity influence treatment response, remains undetermined. Method Observational, ambispective, multicenter, nation-wide, real-world study designed to compare safety/efficacy of OW s.c. 1 mg semaglutide in T2D patients with or without CKD. The influence of CKD severity was also addressed. Patients were followed-up for 12 months. Primary end-points were glycosylated hemoglobin (HbA1c), weight and renal outcomes. Secondary end-points included insulin resistance, atherogenic and hepatic steatosis indexes, and changes in antihyperglycemic medications. Results A total of 296 and 190 T2D patients without or with CKD, respectively, were recruited. Baseline CKD risk was moderate, high or very high in 82, 53 and 45 patients, respectively. Treatment reduced HbA1c by 0.90-1.20%. Relevant differences were seen neither between non-CKD and CKD patients, nor among CKD subgroups. Notable weight losses were achieved in both non-CKD and CKD patients. The median reduction was higher in the former at 6 months (5.90 kg vs. 4.50 kg, P=0.008) and at end of study (6.90 kg vs. 5.00 kg, P=0.087). A trend towards slightly lower weight losses as CKD severity increased was observed. CKD markers improved across all CKD subgroups. Relevant differences were not observed for other variables, either between non-CKD and CKD patients, or among CKD subgroups. Safety concerns were not reported. Conclusions The safety/efficacy of OW s.c. semaglutide to improve glycemic control and weight in T2D patients with CKD is not notably lower than that in T2D patients without renal failure. CKD severity barely influences treatment response. OW s.c. semaglutide can be useful to manage T2D patients with CKD in daily clinical practice.